IgA and IgM protein primarily drive plasma corona‐induced adhesion reduction of PLGA nanoparticles in human blood flow. Issue 2 (22nd May 2017) - Sobczynski, Daniel J.; Eniola‐Adefeso, Omolola
Abstract: The high abundance of immunoglobulins (Igs) in the plasma protein corona on poly(lactic‐co‐glycolic) acid (PLGA)‐based vascular‐targeted carriers (VTCs) has previously been shown to reduce their adhesion to activated endothelial cells (aECs) in human blood flow. However, the relative role of individual Ig classes (e.g., IgG, IgA, and IgM) in causing adhesion reduction remains largely unknown. Here, we characterized the influence of specific Ig classes in prescribing the binding efficiency of PLGA nano‐sized VTCs in blood flow. Specifically, we evaluated the flow adhesion to aECs of PLGA VTCs with systematic depletion of various Igs in their corona. Adhesion reduction was largely eliminated for PLGA VTCs when all Igs were removed from the corona. Furthermore, re‐addition of IgA or IgM to the Igs‐depleted corona reinstated the low adhesion of PLGA VTCs, as evidenced by ∼40–70% reduction relative to particles with an Igs‐deficient corona. However, re‐addition of a high concentration of IgG to the Igs‐depleted corona did not cause significant adhesion reduction. Overall, the presented results reveal that PLGA VTC adhesion reduction in blood flows is primarily driven by high adsorption of IgA and IgM in the particle corona. Pre‐coating of albumin on PLGA VTCs mitigated the extent of adhesion reduction in plasma for some donors but was largely ineffective in general. Overall, this work may shed light into effective control of protein corona composition, thereby enhancing VTC functionality in vivo for eventual clinical use. Abstract : The high abundance of immunoglobulins (Igs) in the plasma protein corona formed on vascular‐targeted carriers (VTCs) has previously been shown to reduce their adhesion to activated endothelial cells. Here, we report that high adsorption of IgA and IgM, and not IgG, primarily drives VTC adhesion reduction in human blood flows.